2020
DOI: 10.1039/c9sm02377a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of cell-generated forces within a multicellular aggregate using microsphere-based traction force microscopy

Abstract: We measure cell-generated forces from the deformations of elastic microspheres embedded within multicellular aggregates. Using a computationally efficient analytical model, we directly obtain the full 3D mapping of surface stresses within minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The ability to robustly model the deformations of compressible materials in the moderate strain regime is required for broad classes of engineering materials, including most biological and biomimetic materials, which typically have a Poisson ratio in the range of 0.2-0.5 and exhibit nonlinear elastic responses [33][34][35][36][37][38]. The ability to accurately relate observed deformations to applied stress fields is particularly important for the development of traction force microscopy methods, which allow determination of cell-generated forces to understand the fundamental mechanobiology, as well as improved disease modeling and design of soft tissue replacements [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to robustly model the deformations of compressible materials in the moderate strain regime is required for broad classes of engineering materials, including most biological and biomimetic materials, which typically have a Poisson ratio in the range of 0.2-0.5 and exhibit nonlinear elastic responses [33][34][35][36][37][38]. The ability to accurately relate observed deformations to applied stress fields is particularly important for the development of traction force microscopy methods, which allow determination of cell-generated forces to understand the fundamental mechanobiology, as well as improved disease modeling and design of soft tissue replacements [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The direct method of determining 3D cell-generated traction stresses circumvents solving an illposed inverse continuum mechanics problem, which requires approximating the measurements with theoretical models 27,57 or computational analyses (e.g., finite element method) 42 . Also, given its mathematical simplicity, the direct method yields traction stresses within a few seconds, including the computations involved in tracking the nanobead displacements with the CPD algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Force resolution to the order of nN Girardo et al, 2018;Mohagheghian et al, 2018;Kaytanli et al, 2020;Vorselen et al, 2020b a clamped membrane subject to a point force (Labernadie et al, 2014). By increasing the thickness of the formvar sheet and thus the substrate stiffness sensed by cells, PFM results demonstrated that leukocyte podosomes increase their protrusive forces in response to stiffer substrates, suggesting that podosomes have a mechanosensing function (Labernadie et al, 2014).…”
Section: Figure 2hmentioning
confidence: 99%
“…However, polystyrene beads are rigid, which makes it impossible to quantify the forces that VECs exert on the beads, and the recent development of methods to quantify mechanical forces in vivo via deformable hydrogel microspheres could overcome this limitation. Inspired by the seminal use of functionalized oil droplets to measure anisotropic stresses within 3-D cell aggregates (Campas et al, 2014), emerging microfabrication methods can now produce deformable hydrogel-based spherical force sensors, with sizes ranging from a few µm up to hundreds of microns (Girardo et al, 2018;Mohagheghian et al, 2018;Kaytanli et al, 2020;Vorselen et al, 2020b; Figure 2H). These elastic microspheres can be employed to study cellular forces induced by specific ligand-receptor interactions, known as microspherebased TFM.…”
Section: Quantifying Tissue-level Cell Forcesmentioning
confidence: 99%